Knowledge Management: the way companies generate, communicate and leverage their intellectual assets. - Choong, Wai Hoong (2004)
The dissertation title is “Knowledge Management: the way companies generate, communicate and leverage their intellectual assets.” The dissertation focuses on how organisations generate knowledge, in terms of information processing or via knowledge creation and innovation. The research also investigates how organisations communicate their acquired knowledge within the organizations’ individuals and groups and the ways organisation leverages their intellectual assets to obtain competitive advantage in the business environment. A critical feature of this research on knowledge management is that it identifies that organisations requires multidisciplinary expertise and learning in order to achieve a complex synergy of highly specialized state-of-the-art technologies and knowledge-creating domains (Dougherty, 1992).Knowledge management can be described as the ability to recognize and manage the system of core competencies required for knowledge-intensive organisations. It requires a welldefined framework that relates investment in expertise and internal competencies to organisation performance. Knowledge creates knowledge when it is shared (Lang, 2001). By sharing knowledge for individual and corporate access, the knowledge of an organisation reaches a higher level than the sum of the individuals’ knowledge. Knowledge, therefore, creates more value when it is used and transformed into organisational knowledge (Ekstedt,1988). Although, this research identified that successful knowledge management implementation is mainly linked to organisational culture and people, however few framework of best practice of knowledge management has emerged from these organisations introducing knowledge management programmes in their business strategy.